3D/1D Amine Functionalized MIL-125/TiO2 NWs Metal-organic Framework Heterostructures for Solar Stimulated CO2 Reduction to Green Fuels - Ji Zhang Tai; Wei Keen Fan; Hajar Alias; Amnani Shamjuddin; Mohamad Sukri Mohamad Yusof; Abdul Rahman Mohamed; Muhammad Tahir (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The urgent need to mitigate atmospheric CO2 and transition toward renewable energy has spurred growing interest in photocatalytic CO2 hydrogenation. In this work, we report on the fabrication of a novel 3D/1D NH2-MIL-125/TiO2 nanowire (NWs) heterostructure via a straightforward mechanical assembly method, combining the excellent visible light absorption of amino-functionalized metal-organic frameworks (MOFs) with the robust charge transport properties of one-dimensional TiO2 NWs. Structural and optical characterisations have confirmed on intimate interfacial contact and synergistic electronic interactions between the MOF and TiO2, forming an S-scheme heterojunction which promotes an enhanced photogenerated carrier separation. Under visible light, the optimised 5 wt% NH2-MIL-125/TiO2 NWs composite achieved methane and CO yields of 13.98 μmol/g and 84.76 μmol/g, respectively. Notably, CH4 production soared to 660.47 μmol/g under solar-simulated irradiation, representing a 47-fold enhancement. This significant performance boost is attributed to improved light harvesting, facilitated electron migration, and strengthened interfacial dynamics. This study provides a scalable and efficient strategy for designing hybrid MOF-semiconductor photocatalysts, offering a promising pathway for sustainable solar fuel generation. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).